Multiple compensatory mutations contribute to the de‐domestication of Iberian weedy rice. Issue 5 (4th July 2022) - Li, Xiang; Zhang, Shulin; Amaro‐Blanco, Ignacio; Perera, Sherin; Khandekar, Nikhil Shirish; Lowey, Daniel; Osuna, Maria Dolores; Caicedo, Ana L.
Abstract : Societal Impact Statement: Weedy plants are a major constraint on agricultural productivity. Weedy rice is a weed that invades rice fields worldwide and is responsible for reductions in rice yields. Studies to date have detected multiple independent weedy rice origins in different parts of the world. We investigated the origin of weedy rice in Spain and Portugal and found that it has evolved from a cultivated rice variety group grown locally. Iberian weeds carry mutations that reverse domesticated pericarp color to its ancestral red color. Our results imply that management strategies are needed to prevent the evolution of troublesome weeds from cultivated ancestors. Summary: Weedy rice, a damaging conspecific weed of cultivated rice, has arisen multiple times independently around the world. Understanding all weedy rice origins is necessary to create more effective weed management strategies. The origins of weedy rice in Spain and Portugal, where there are no native Oryza species, are unknown. In this study, we try to identify the likely ancestors of Iberian weedy rice and the mechanisms involved in the evolution of two weedy traits, seed shattering, and red pericarps. We used genotyping by sequencing to understand the origin of Iberian weedy rice and its relationship to other weedy, wild, and cultivated rice groups worldwide. We also genotyped candidate genes for shattering and pericarp color. We find that weedy rice in the Iberian Peninsula has primarily evolved through de‐domestication of temperate japonica cultivars, with minor origins from exotic weedy rice. Iberian weeds have evolved the capacity to shatter seeds via novel loci and have acquired red pericarps via compensatory mutations in the Rc domestication gene. Our results suggest the Iberian weeds have experienced selection at multiple locations in the genome to establish as weeds, likely targeting male fertility genes among other functions. Our characterization of Iberian weedy rice adds to the growing evidence that de‐domestication of cultivated rice varieties is the main source of weedy rice worldwide. Their evolutionary versatility explains why weedy rice continues to be one of the most problematic weeds of cultivated rice. Abstract : Weedy plants are a major constraint on agricultural productivity. Weedy rice, a weedy type of rice, invades rice fields worldwide and is responsible for reductions in rice yields. Studies to date have detected multiple independent weedy rice origins in different parts of the world. We investigated the origin of weedy rice in Spain and Portugal and found that it has evolved from a cultivated rice variety group grown locally. Iberian weeds carry mutations that reverse domesticated pericarp color to its ancestral red color. Our results imply that management strategies are needed to prevent the evolution of troublesome weeds from cultivated ancestors. Abstract : Las malezas son uno de los limitantes principales para la productividad agrícola. El arroz maleza es una maleza que invade los campos de arroz en todo el mundo, llevando a reducciones en los rendimientos del cultivo. Varios estudios han detectado múltiples orígenes independientes de arroz maleza en diferentes partes del mundo. Aquí investigamos el origen del arroz maleza en España y Portugal y descubrimos que ha evolucionado a partir de variedades de arroz cultivadas localmente. Las malezas ibéricas llevan mutaciones que revierten el color blanco de la semilla domesticada a su color rojo ancestral. Nuestros resultados resaltan la necesidad de estrategias de manejo para prevenir la evolución de malezas a partir de ancestros cultivados.